1992
DOI: 10.1152/ajpcell.1992.262.2.c422
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-contraction coupling in pigs heterozygous for malignant hyperthermia

Abstract: A defect in the skeletal muscle sarcoplasmic reticulum (SR) calcium release channel of malignant hyperthermia-susceptible (MHS) pigs greatly enhances SR calcium release in pigs homozygous for the malignant hyperthermia (MH) gene. In pigs heterozygous at this locus, rates of calcium release from isolated SR stimulated by Ca2+, ATP, or caffeine are intermediate to those of both MHS and normal SR [Mickelson et al. Am. J. Physiol. 257 (Cell Physiol. 26): C787-C794, 1989]. In this study bundles of intact muscle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 15 publications
7
27
0
Order By: Relevance
“…Its distinctive properties are: 1) it is initiated by depolarization; 2) it is dependent on the presence of both RyR1 and DHPR; 3) it is independent of the DHPR L-type Ca 2ϩ current; 4) it does not depend on SR Ca 2ϩ release; and 5) it can be effectively inhibited by La 3ϩ or SKF96365 (24). Previous studies of KCl responses in MH muscle cells showed significantly larger muscle contractures and lower KCl contracture thresholds in muscle fibers dissected from MH susceptible swine compared with WT (42)(43)(44). In addition, it has been reported that the total calcium transient in MH susceptible muscle fibers was larger than control fibers when exposed to subcontracture and contracture concentrations of KCl (30,43,45,46 This is most easily detectable during the sustained phase that follows the peak of the Ca 2ϩ transient.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Its distinctive properties are: 1) it is initiated by depolarization; 2) it is dependent on the presence of both RyR1 and DHPR; 3) it is independent of the DHPR L-type Ca 2ϩ current; 4) it does not depend on SR Ca 2ϩ release; and 5) it can be effectively inhibited by La 3ϩ or SKF96365 (24). Previous studies of KCl responses in MH muscle cells showed significantly larger muscle contractures and lower KCl contracture thresholds in muscle fibers dissected from MH susceptible swine compared with WT (42)(43)(44). In addition, it has been reported that the total calcium transient in MH susceptible muscle fibers was larger than control fibers when exposed to subcontracture and contracture concentrations of KCl (30,43,45,46 This is most easily detectable during the sustained phase that follows the peak of the Ca 2ϩ transient.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies of KCl responses in MH muscle cells showed significantly larger muscle contractures and lower KCl contracture thresholds in muscle fibers dissected from MH susceptible swine compared with WT (42)(43)(44). In addition, it has been reported that the total calcium transient in MH susceptible muscle fibers was larger than control fibers when exposed to subcontracture and contracture concentrations of KCl (30,43,45,46 This is most easily detectable during the sustained phase that follows the peak of the Ca 2ϩ transient. The data from our previous study on seven common MH RyR1s expressed in dyspedic myotubes gave us the first clue that the kinetics of MH-associated Ca 2ϩ transients, especially the sustained phase, is significantly different compared with WT RyR1 myotubes (30).…”
Section: Discussionmentioning
confidence: 94%
“…Several different preparations have been utilized for functional analysis of caffeine sensitivity of MH RyR1. These have included measurements of caffeine-induced Ca 2ϩ release from heavy SR membranes prepared from MH pig muscles (26), as well as cellular responses to caffeine utilizing either cultured primary myotubes prepared from human or pig muscle biopsies (22,27), or non-muscle cells expressing MH RyR1s (12). Collectively these diverse preparations have shown that an increased caffeine sensitivity was a common characteristic for each MH mutation.…”
Section: Heightened Efficacy Of Caffeine Toward Mh Ryr1s At Resting Imentioning
confidence: 99%
“…This difference was consistent with the previously documented higher twitch-totetanus ratio in MHS as compared with normal muscles. 7,9 In spite of this difference in tension at low frequencies, the degree of fusion at each stimulus frequency was not significantly different between the two muscle types at 36°C (see Fig. 2A).…”
Section: Resultsmentioning
confidence: 88%
“…In MHS muscles the mechanical threshold is lower, twitch-to-tetanus ratio is greater, and sensitivity to a number of drugs is enhanced 9 in comparison to normal muscles. However, other predicted alterations in contractile properties have not been observed.…”
mentioning
confidence: 98%